2020
DOI: 10.1248/bpb.b20-00373
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Calcitonin Gene-Related Peptide and Adrenomedullin Receptors by PEGylated Adrenomedullin

Abstract: Adrenomedullin (AM) improves colitis in animal models and patients with inflammatory bowel disease. We have developed a PEGylated AM derivative (PEG-AM) for clinical application because AM has a short half-life in the blood. However, modification by addition of polyethylene glycol (PEG) may compromise the function of the original peptide. In this paper, we examined the time course of cAMP accumulation induced by 5 and 60 kDa PEG-AM and compared the activation of calcitonin gene-related peptide (CGRP), AM1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…As expected, Fc-AMs were less active in the cAMP assay compared with AM. We produced various analogs of PEG-AM whose N-terminus was attached to various sizes of PEG [ 23 , 24 ]. We found that the activity decreased as the molecular weight of PEG-AM increased.…”
Section: Discussionmentioning
confidence: 99%
“…As expected, Fc-AMs were less active in the cAMP assay compared with AM. We produced various analogs of PEG-AM whose N-terminus was attached to various sizes of PEG [ 23 , 24 ]. We found that the activity decreased as the molecular weight of PEG-AM increased.…”
Section: Discussionmentioning
confidence: 99%